2014
DOI: 10.1371/journal.pone.0113142
|View full text |Cite
|
Sign up to set email alerts
|

Holy Smoke in Medieval Funerary Rites: Chemical Fingerprints of Frankincense in Southern Belgian Incense Burners

Abstract: Frankincense, the oleogum resin from Boswellia sp., has been an early luxury good in both Western and Eastern societies and is particularly used in Christian funerary and liturgical rites. The scant grave goods in late medieval burials comprise laterally perforated pottery vessels which are usually filled with charcoal. They occur in most regions of western Europe and are interpreted as incense burners but have never been investigated with advanced analytical techniques. We herein present chemical and anthraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 62 publications
(80 reference statements)
0
12
0
1
Order By: Relevance
“…This acidic part was further fractionated by successive flash chromatography on silica gel and AgNO 3 coated silica gel, and eventually by HPLC.Inthis last series of separations,t he most efficient way to quickly localize this odorant in the chromatographic fractions proved to be their direct olfactory evaluation, on smelling strips dipped in the chromatographic tubes.I ndeed, their TLC,G C-MS,a nd HPLC-UV analyses were not particularly helpful, as none of the corresponding detection systems was sensitive enough, compared to the human nose.Eventually,about 1mgofabout a94:6mixture of the two suspected odorants was obtained at RI DB-WAX = 2546 and 2538. 1 Hand 13 CNMR, as well as COSY, HSQC and HMBC experiments suggested that the main component of this mixture was 2-octylcyclopropyl-1-carboxylic acid. This structure was consistent with the existence of two (trans and cis)i somers (1-2), and could explain the presence of two closely eluting peaks showing similar mass spectra.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…This acidic part was further fractionated by successive flash chromatography on silica gel and AgNO 3 coated silica gel, and eventually by HPLC.Inthis last series of separations,t he most efficient way to quickly localize this odorant in the chromatographic fractions proved to be their direct olfactory evaluation, on smelling strips dipped in the chromatographic tubes.I ndeed, their TLC,G C-MS,a nd HPLC-UV analyses were not particularly helpful, as none of the corresponding detection systems was sensitive enough, compared to the human nose.Eventually,about 1mgofabout a94:6mixture of the two suspected odorants was obtained at RI DB-WAX = 2546 and 2538. 1 Hand 13 CNMR, as well as COSY, HSQC and HMBC experiments suggested that the main component of this mixture was 2-octylcyclopropyl-1-carboxylic acid. This structure was consistent with the existence of two (trans and cis)i somers (1-2), and could explain the presence of two closely eluting peaks showing similar mass spectra.…”
mentioning
confidence: 88%
“…It was burned as incense in ad omestic context and during religious ceremonies in the old Civilizations of Arabia, Mesopotamia, Persia, and Egypt, and later in Greece and Roma. [1] This extremely early history of use is supported by substantial archaeochemical evidence,t hanks to the stability of specific constituents of frankincense which could be detected in various containers and incense burners in archeological sites of Egypt, Yemen, France,and Belgium. [1,3] Frankincense is mentioned 22 times in the Bible,notably as one of the presents offered to the Christ by the three Wise Men, and its use as incense has been perpetuated up to the present in Christian religious ceremonies.I ndeed, its typical odor is frequently associated with the "smell of old churches" [4] as churches today are the only places in Occident where frankincense is used as asingle fragrant ingredient.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, their use might be almost as old as the domestication of fire. Among these materials, frankincense (also known as olibanum) has a history dating back to the late 4th millennium B.C., and has been often considered as one of the first aromatic materials used by humans . This gum resin naturally exudes from the bark of Boswellia species (Burseraceae), which grows mostly in arid mountainous regions on both sides of the Gulf of Aden and the Red sea.…”
Section: Figurementioning
confidence: 99%
“…; Reber and Hart ; Reber and Kerr ; Baeten et al . ). The high proportion of saturated hydrocarbon moieties present in lipids reduces their structural modification and degradation over time owing to their inherent hydrophobicity and entrapment within a ceramic matrix, thereby making them excellent candidates as biomarkers (Evershed , ).…”
Section: Introductionmentioning
confidence: 97%